2016
DOI: 10.1007/s10238-016-0413-6
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor (G-CSF) increases histone-complexed DNA plasma levels in healthy volunteers

Abstract: Granulocyte colony-stimulating factor (G-CSF) is an activator of neutrophil granulocytes. Neutrophil extracellular traps are a defensive mechanism consisting of neutrophils, platelets, DNA, histones and antimicrobial proteins. This study was performed to determine whether G-CSF increases histone-complexed DNA in the plasma of healthy volunteers. In total, 51 healthy volunteers (25 males and 26 females) were treated with G-CSF (18 with 300 µg single dose i.v., 27 with 5 µg/kg s.c. for 4 days) and six participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…We did not find a sex difference in the number of neutrophils in the blood following rG-CSF treatment in naïve mice. This finding is in contrast to clinical findings in healthy volunteers; Schoergenhofer et al (2017) identified more plasma neutrophil histone-complexed DNA in the men compared to women after a single of rG-CSF. Consistent with our previous reports in the 4NQO model (Scheff et al, 2018), there is a sex difference in neutrophil infiltration in saline-treated mice with HSC-3 tumors.…”
Section: Discussioncontrasting
confidence: 89%
“…We did not find a sex difference in the number of neutrophils in the blood following rG-CSF treatment in naïve mice. This finding is in contrast to clinical findings in healthy volunteers; Schoergenhofer et al (2017) identified more plasma neutrophil histone-complexed DNA in the men compared to women after a single of rG-CSF. Consistent with our previous reports in the 4NQO model (Scheff et al, 2018), there is a sex difference in neutrophil infiltration in saline-treated mice with HSC-3 tumors.…”
Section: Discussioncontrasting
confidence: 89%
“…G-CSF treatment in humans has been associated with the elevation of markers of systemic NET formation (47) and increased G-CSF levels have been previously correlated with NET-associated microthrombosis in cancer patients (17, 27). More recently, biomarkers of the systemic formation of NETs were associated with the occurrence of venous thromboembolism in certain cancer types (18).…”
Section: Discussionmentioning
confidence: 99%
“…NETs cause platelet aggregation, thrombin activation, and fibrin clot formation (64). Building upon these observations, since administration of G-CSF to healthy volunteers increases NET levels (65), one possible hypothesis is that G-CSF use in HCT recipients may predispose to or perpetuate TA-TMA, though to date there are no data analyzing this potential risk factor. Fungal infections, especially aspergillus, have been linked to TA-TMA (6, 16), possibly mediated via the same pathway by which the angioinvasion process leads to endothelial activation.…”
Section: Risk Factorsmentioning
confidence: 99%